MICROFINANCE DEVELOPMENT BASED LOCAL WISDOM: LEARNING FROM THE RINJUNG PAHAMU ASSOCIATION OF FARMERS GROUPS - Huruta, Bernard Edheney; Pratomo, Yulius (Sebelas Maret University, 2019)
This study aims to describe the form of local wisdom in rural microfinance in overcoming the problem of access to financial services. This is in line with the government's financial inclusion program for rural residents in remote areas, especially in East Sumba Regency. Methodically, this study used qualitative methods to picturize the phenomenon of local wisdom-based microfinance development in rural communities. The results of the study show that the local wisdom experienced by the members of the Rinjung Pahamu Association of Farmers Groups was used to overcome the limited access to formal financial services. The forms of microfinance developed on the island of Sumba could not be separated from the appreciation of the noble values (Marapu) adopted by the community, such as the philosophy of Pawandang, the cage must not be empty and Rotu padang. Furthermore, savings and loan activities carried out in the management of the Association of Farmers Groups always consider aspects of justice and survival.